2011
DOI: 10.1177/0734242x10390730
|View full text |Cite
|
Sign up to set email alerts
|

Review Article: Persistent organic pollutants and landfills - a review of past experiences and future challenges

Abstract: The landfilling and dumping of persistent organic pollutants (POPs) and other persistent hazardous compounds, such as polychlorinated biphenyls (PCBs), hexachlorocyclohaxane (HCH), polybrominated diphenylether (PBDEs) or perfluorooctane sulfonic acid (PFOS) can have significant adverse environmental consequences. This paper reviews past experiences with such disposal practices and highlights their unsustainability due to the risks of contamination of ecosystems, the food chain, together with ground and drinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
106
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(129 citation statements)
references
References 70 publications
1
106
1
Order By: Relevance
“…Most PCDD/Fs are initially formed during the combustion of fossil fuels and are then emitted into the air (Weber et al 2011). Therefore, monitoring PCDD/Fs in the air is a key issue for controlling the dispersal of these compounds into other environmental compartments, such as water and soil, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Most PCDD/Fs are initially formed during the combustion of fossil fuels and are then emitted into the air (Weber et al 2011). Therefore, monitoring PCDD/Fs in the air is a key issue for controlling the dispersal of these compounds into other environmental compartments, such as water and soil, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Pollution by organic compounds is also a concern emerging from studies designed to address the topic of sealed landfills, as many recently banned compounds, dumped in landfills and numerous affected ecosystems, have been detected [26]. The organic compounds determined in the soil samples and the techniques used for this purpose were: total hydrocarbons by infrared spectrometry (UNE 77307); organochlorine insecticides and polychlorinated biphenyls (PCBs) by gas chromatography (ISO 10382); and polycyclic aromatic hydrocarbons (PAHs) (ISO 18287) and phenols (U.S. E.P.A 3550B, U.S. E.P.A 3650B and U.S. E.P.A 8401) by gas chromatography.…”
Section: Organic Compoundsmentioning
confidence: 99%
“…The environmental risks of EPS or XPS insulation waste containing HBCDD in landfill sites cannot be neglected Substance flow analysis in Japan and Switzerland highlights landfills as long-term sources of HBCDD release (Managaki et al 2009;Morf et al 2008;Weber et al 2011). Earlier studies have also generally found release of BFRs from landfills in Sweden, Japan, and Canada, where HBCDD was widely detected in the environmental mediums, and in Sweden, the HBCDD in the water, air, and sediment of the landfill is detected to be 3∼9 ng/L, 0.013∼0.18 ng/m 3 , and <0.1 μg/kg d.w. (Remberger et al 2004;Danon-Schaffer et al 2014;Osako et al 2004).…”
Section: Landfilling and Incinerationmentioning
confidence: 99%